Genetic background limits generalizability of genotype-phenotype relationships - Sittig, Laura J. (Neuron, 2016)
Genome wide association studies (GWAS) have identified numerous loci that influence risk for psychiatric diseases. Genetically engineered mice are often used to characterize genes implicated by GWAS. These studies are based on the assumption that observed genotype-phenotype relationships will generalize to humans, implying that the results would at least generalize to other inbred mouse strains. Given current concerns about reproducibility we sought to directly test this assumption. We produced F(1) crosses between male C57BL/6J mice heterozygous for null alleles of Cacna1c and Tcf7l2 and wild-type females from 30 inbred laboratory strains. We found extremely strong interactions with genetic background that sometimes supported diametrically opposing conclusions. These results do not negate the invaluable contributions of mouse genetics to biomedical science, but they do show that genotype-phenotype relationships cannot be reliably inferred by studying a single genetic background, and thus constitute a major challenge to the status quo.